A Quantitative Examination of Factors that Influence Technology Integration in Higher Education System - Hicham Laabidi; Youssouf Laabidi (Indonesian Journal of EFL and Linguistics, 2016)
The purpose of this paper is to explore and describe the status of technology integration in Moroccan higher education system. Forty-six university English language teachers were selected from two universities: Moulay Ismail University Faculty of Arts and Humanities – Meknes and Sidi Mohamed Ben AbdellahDahr – El Mahraz – Fes . The quantitative data was analysed using descriptive statistics of frequencies and percentages. The findings revealed that teachers consider Information and Communication Technology very essential in their teaching. The results also showed that computer technology is integrated in Moroccan universities at low levels. This lack of use of the new technologies in instruction and learning was attributed to several barriers including insufficient professional development, inadequate access to computer technologies, and lack of computer training to name only few.